Operationalizing Learning from Rare Events: Framework for Middle Humanitarian Operations Managers. Issue 9 (10th June 2019) - Labib, Ashraf; Hadleigh‐Dunn, Sara; Mahfouz, Amr; Gentile, Marco
Abstract : The purpose of this paper is to investigate the learning from rare events and the knowledge management process involved, which presents a significant challenge to many organizations. This is primarily attributed to the inability to interpret these events in a systematic and "rich" manner, which this paper seeks to address. We start by summarizing the relevant literature on humanitarian operations management (HOM), outlining the evolution of the socio‐technical disaster lifecycle and its relationship with humanitarian operations, using a supply chain resilience theoretical lens. We then outline theories of organizational learning (and unlearning) from disasters and the impact on humanitarian operations. Subsequently, we theorize the role of middle managers in humanitarian operations, which is the main focus of our paper. The main methodology incorporates a hybrid of two techniques for root cause analysis, applied to two related case studies. The cases were specifically selected as, despite occurring twenty years apart, there are many similarities in the chain of causation and supporting factors, potentially suggesting that adequate learning from experience and failures is not occurring. This provides a novel learning experience within the HOM paradigm. Hence, the proposed approach is based on a multilevel structure that facilitates the operationalization of learning from rare events in humanitarian operations. The results show that we are able to provide an environment for multiple interpretations and effective learning, with emphasis on middle managers within a humanitarian operations and crisis/disaster management context.